Patch testing in Iranian patients: A ten-year experience - Davoudi Masoud; Firoozabadi Mehdi; Gorouhi Farzam; Zarchi Ali Akbar; Kashani Mansour; Dowlati Yahya; Firooz Alireza (Wolters Kluwer Medknow Publications, 2006)
Background: Allergic contact dermatitis is a common inflammatory skin disease, which may occur as a result of exposure to specific allergens. Genetic and allergen exposure variations are determinants of different frequency of sensitization in different countries. The objective of this study was to determine the frequency of sensitization to contact allergens in the Iranian patients with dermatitis. Materials and Methods: We analyzed our patch-test database in a referral skin clinic in Tehran, Iran, retrospectively. All patients patch-testing with a clinical diagnosis of contact dermatitis and/or atopic dermatitis over a 10-year period (1993 to 2002) were included. The 23-allergen European standard series (ESS) screening has been used for evaluation in all the patients. Results: Data were available from a total of 222 patients. Out of them, 145 patients (65.3%) showed at least one positive reaction and 34 patients (15.3%) had more than two positive reactions. The five most common allergens were: nickel sulfate 50 (22.6%), cobalt chloride chloride 32 (14.5%), fragrance mix 30 (13.6%), potassium dichromate 21 (9.5%) and neomycin sulfate 20 (9.0%). Contact allergy to nickel sulfate was significantly more common in females and in younger patients ( P < 0.05). Fragrance mix was the most common allergen in male patients, but there was no significant difference in its frequency between males and females. Conclusion: The ESS seems to be suitable for patch testing patients in Iran. Nickel sulfate was found to be the most common contact allergen in Iran, mostly affecting women and younger patients probably due to more exposure.